Circulating levels of adipokines and hormones in periparturient primiparous Sahiwal cows - PANDEY, VIJAY; NIGAM, RAJESH; SINGH, SATYENDRA PAL; SHARMA, DEEPAK; TIWARI, MADHU; CHAUDHARY, SOUMEN (The Indian Journal of Animal Sciences, 2019)
The circulating levels of adipokines and other hormones were determined in periparturient Sahiwal cows. Blood samples were collected from 6 Sahiwal cows during periparturient period (–30 to +90 days) at 15 days interval. The results revealed decrease in adiponectin, leptin and progesterone levels from pregnancy to parturition which subsequently increased to prepartum levels. The resistin and estrogen levels increased from pregnancy to parturition and reduced to prepartum levels during lactation. Adiponectin levels showed positive association with average milk yield (AMY) and leptin while negative association with estrogen; resistin revealed positive association with estrogen and negative with AMY and leptin and leptin showed positive association with AMY, adiponectin and resistin and negative with estrogen. In conclusion, the study provides data on plasma levels of adipokines in primiparous periparturient cows that may be useful for clinical and experimental interpretation and significant association among adipokines, lipid profile and AMY indicating their significant role in lactogenesis.